2017
DOI: 10.1080/10888705.2017.1376204
|View full text |Cite
|
Sign up to set email alerts
|

Behavior and Performance of Dairy Cows After Transfer from Tied to Cubicle Housing

Abstract: Behavior and performance changes when tied dairy cows were moved to a loose housing system in a cubicle system were investigated. Behavioral observations were made for 3 consecutive days in 3 periods after transition. The cows (n = 105) were observed on 18 sampling occasions for 1 month. Recordings were made of body positions and general and social behaviors. Monthly milk records were collected 1 year before and 1 year after transition. Cows walked more during the 1st observation period than during the other p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 14 publications
3
13
1
Order By: Relevance
“…Rumination, drinking and eating did not show any significant difference among treatments. Rumination and eating were the most common active behaviors and, as observed in other studies [31,32], time spending rumination was less compared to eating regardless of the treatment group. Pavlenko et al [32] showed that when dairy cows were transferred to a new and unfamiliar housing, they performed more rumination and walking and less eating during the first 3 d, and then it was reversed afterwards.…”
Section: Time (H) U-o 1) (A) T-o (B) U-p (C) T-p (D) (B-a) (D-supporting
confidence: 77%
See 1 more Smart Citation
“…Rumination, drinking and eating did not show any significant difference among treatments. Rumination and eating were the most common active behaviors and, as observed in other studies [31,32], time spending rumination was less compared to eating regardless of the treatment group. Pavlenko et al [32] showed that when dairy cows were transferred to a new and unfamiliar housing, they performed more rumination and walking and less eating during the first 3 d, and then it was reversed afterwards.…”
Section: Time (H) U-o 1) (A) T-o (B) U-p (C) T-p (D) (B-a) (D-supporting
confidence: 77%
“…Rumination and eating were the most common active behaviors and, as observed in other studies [31,32], time spending rumination was less compared to eating regardless of the treatment group. Pavlenko et al [32] showed that when dairy cows were transferred to a new and unfamiliar housing, they performed more rumination and walking and less eating during the first 3 d, and then it was reversed afterwards. More importantly, forage NDF source at a similar level did not impact growth performance but both forage source and inclusion level influenced feeding behavior as cattle consuming bulkier forages (wheat straw or corn stover) or at greater inclusion levels had a higher eating time [26].…”
Section: Time (H) U-o 1) (A) T-o (B) U-p (C) T-p (D) (B-a) (D-supporting
confidence: 77%
“…For example, increased calling is observed during estrus (Schön et al, 2007), where any link to affect is unclear. Increased vocalizations have also been observed in cows transitioned from tiestalls to freestalls (Pavlenko et al, 2018) and in calves during social play (Wagner et al, 2013), suggesting that a vocal response is not specific to negative events. Moreover, vocal responses are highly variable among individuals even in response to clearly negative events.…”
Section: Behavioral Responsesmentioning
confidence: 99%
“…Our results showed similar trend with other research results. 12,13 Cows in oestrus display the many behaviors more intensively: restlessness, mounting, allowing mounting without standing, sniffing the vulva of another cow, resting the chin on the back of another cow, licking, rubbing, and aggressiveness. Many technologic aids try to use Oestrus detection generally depends on behavioral changes of cows such as standing, mounting, walking, restlessness, chin pressing to detect oestrus.…”
Section: Resultsmentioning
confidence: 99%
“…It is also suspected that the vocalizations of cattle contain information about age, sex, dominance status, and stage in the estrous cycle. 11 Increased vocalizations have also been observed in cows transitioned from tie stalls to free stalls 12 and in calves during social play, 13 suggesting that a vocal response is not specific to negative events. Moreover, vocal responses are highly variable among individuals even in response to clearly negative events.…”
Section: Introductionmentioning
confidence: 99%